Peranan Guru Dalam Membina Karakter Peserta Didik SMA Untuk Peduli Lingkungan - Henny Siswindah Lumbantobing; Ulung Napitu; Tioner Purba; Ease Arent; Rima Meilitasari (Journal on Education, 2023)
The purpose of this study was to understand the role of teachers in developing environmental care personalities in high school students and to describe the implementation of a waste-free program. The type of research used is descriptive qualitative method. The tool used is about the teacher's role in developing the disposition of high school students to care about the environment through the collection of interview data, observations, and recordings in a waste-free program. The findings of this study are the teacher's role in developing students' dispositions to care for the environment in a waste-free program and carry out and carry out their roles; 1) The teacher as a motivator provides encouragement and enthusiasm to handle waste. 2) Teachers act as facilitators to guide environmental care and provide cleaning tools in every school environment. 3) The teacher acts as a whistle blower to provide information about the importance of a clean environment, especially minimizing plastic waste. 4) The teacher acts as an evaluator to evaluate the results of the waste-free program. 5) Taking the teacher as an example, namely making the teacher a good example for students, because the teacher is basically a figure who is admired and imitated. 6) Teachers as educators, namely teachers in the learning system apply environmentally friendly learning.